Gastrodiplomasi dan Identitas Nasional: Studi Thailand, Vietnam, dan Singapura - Ilham Surya Pratama; Roby Rakhmadi; Kevin Hansen Tamba (Jurnal Terekam Jejak, 2024)
A country's cuisine is a fundamental component of its identity and culture because it captures the spirit of its customs, history, and values. Food can be readily communicated with people worldwide in an era of increased mobility, globalization, and technology. This has led to the growth of "gastrodiplomacy," a growingly popular cultural diplomacy tactic employed by nations to support nation-building and nation branding. Nonetheless, there is still a dearth of academic research on this subject. In order to respond to the above query, this essay examines three case studies of gastrodiplomacy initiatives in Thailand, Vietnam, and Singapore: What are the similarities and differences between these three Asian countries' efforts in gastrodiplomacy? This article indicates that, despite the fact that gastrodiplomacy is typically linked to cultural diplomacy, the political and social climate of a nation, as well as both local and international interests, have a significant impact on the practice's effectiveness and degree of success. The investigation makes the case that despite their best efforts, Vietnam and Singapura were unable to replicate Thailand's reasonably successful gastrodiplomacy campaign because to factors including political turmoil and a lack of popular support. In the end, as nations want to reinvent their gastrodiplomacy efforts, these obstacles are propelling new methods of doing so.